A study on presentation and management of ectopic pregnancy at tertiary care hospital - Singh, Tarini; Mohan, Sanil; Aggarwal, Shikha; Maji, Debkalyan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Ectopic pregnancy and its consequences are the most severe form of obstetric emergency during first trimester of pregnancy. It is a kind of life threatening emergency leading to significant maternal morbidity and even mortality. Methods: A prospective study was conducted at a tertiary care teaching hospital of Northern India from 01 Jan 2020 to 31 Mar 2020. All cases of ectopic pregnancy which were admitted and managed during this study period were included in the study. All collected data were analysed with Epitable 6.04 version and SPSS version 20 software. Results: During the study period total 32 cases of ectopic pregnancy were studied. Classical symptoms of amenorrhoea, pain abdomen and bleeding per vaginum were observed in 62.50% cases whereas 93.75% cases were associated with pain abdomen only and 71.88% cases had the symptoms of bleeding per vaginum only. All cases were managed surgically. The incidence of ectopic pregnancy was one in 200 delivered pregnancy. Most case were multiparas and common in 27 -32 yr age group (53.13%). Tubal ectopic pregnancy was common in right side (63%). Approximately 81% cases presented with haemoperitoneum and 63% cases required blood transfusion. Conclusions: Ectopic pregnancy mostly presents as an obstetrics emergency in our hospital especially with rupture ectopic pregnancy with haemoperitoneum. Early diagnosis and intervention suited best for the situation is mainstay for favourable and successful outcome.